8(x+6)+6(x+6)=6x-6

Simple and best practice solution for 8(x+6)+6(x+6)=6x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(x+6)+6(x+6)=6x-6 equation:


Simplifying
8(x + 6) + 6(x + 6) = 6x + -6

Reorder the terms:
8(6 + x) + 6(x + 6) = 6x + -6
(6 * 8 + x * 8) + 6(x + 6) = 6x + -6
(48 + 8x) + 6(x + 6) = 6x + -6

Reorder the terms:
48 + 8x + 6(6 + x) = 6x + -6
48 + 8x + (6 * 6 + x * 6) = 6x + -6
48 + 8x + (36 + 6x) = 6x + -6

Reorder the terms:
48 + 36 + 8x + 6x = 6x + -6

Combine like terms: 48 + 36 = 84
84 + 8x + 6x = 6x + -6

Combine like terms: 8x + 6x = 14x
84 + 14x = 6x + -6

Reorder the terms:
84 + 14x = -6 + 6x

Solving
84 + 14x = -6 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
84 + 14x + -6x = -6 + 6x + -6x

Combine like terms: 14x + -6x = 8x
84 + 8x = -6 + 6x + -6x

Combine like terms: 6x + -6x = 0
84 + 8x = -6 + 0
84 + 8x = -6

Add '-84' to each side of the equation.
84 + -84 + 8x = -6 + -84

Combine like terms: 84 + -84 = 0
0 + 8x = -6 + -84
8x = -6 + -84

Combine like terms: -6 + -84 = -90
8x = -90

Divide each side by '8'.
x = -11.25

Simplifying
x = -11.25

See similar equations:

| x+3+5x-8= | | 2x*(x+5)=0 | | 2y^4(4y+1)(y-2)=0 | | -1/2x-3=-1/2x-10 | | 2x^2+4x*sqrt(1-x^2)-1=0 | | (x-9)+(2x+29)+(x)=180 | | 5(2z-4)=8(z+3) | | 8x+9=13x-6 | | 5y^4(3y^2-12y)(y-4)= | | (-1)-(-9)= | | 3b=9-a | | 10x+1=2x+57 | | 1/2x-3=1/2x-10 | | p-8=5p | | 5l+5w=42 | | X+25+X+30=180 | | 2x+2y=2000 | | 5y=8(5y-7) | | 1/2x-10=1/2x-3 | | 2x(3x-4)=2x(3x+8) | | 21-y=26 | | 14+0.3333x=40 | | 3x/7=2/7=2 | | 0.1=cos(x) | | 7/4-7/3 | | 8n^2-10n-3=0 | | 5/3-4 | | 3(x+10)=2x+30 | | -3x^3-9x^2-6x=0 | | 2(4x-9)=7(x-2) | | (1/3)(2/5)-45 | | 42-3x=12-9 |

Equations solver categories